The effects of growth, maturation and training on strength and power development in young artistic female gymnasts - Moeskops, S. (Cardiff Metropolitan University, 2020)
Female artistic gymnastics demands a combination of physical abilities including strength, power and speed to perform a diverse set of skills. Although gymnasts' training typically commences early in the prepubertal years, very little is known about how these physical qualities develop due to the interaction of maturation and training and how these measures influence vaulting performance. Chapter 3 showed that within- and between-session measures of absolute (PFabs) and relative peak force (PFrel) from an isometric mid-thigh pull (IMTP) test were reliable for both pre-peak height velocity [PHV] (CV = 9.4%, ICC = 0.87) and post-PHV (CV = 7.3%, ICC = 0.92). However, systematic bias was evident between-sessions 1 and 2 in the pre-PHV group. Therefore, the IMTP was deemed a reliable method of measuring peak force in pre- and post-PHV female athletes, providing that pre-PHV athletes attend an additional familiarisation session. Chapters 4-6 revealed that the majority of absolute isometric and dynamic force-time variables from the IMTP and jumping protocols increase with maturation. The IMTP results showed PFabs and absolute force at various time epochs were significantly greater in the most mature cohort compared to the least mature group of gymnasts (p < 0.05; all d > 0.60). Vertical jumping performance improved with biological maturity, as evidenced by the most mature gymnasts' producing significantly more absolute force (p < 0.05; all d > 0.78), impulse (p < 0.05; all d > 0.75), power (p < 0.05; all d > 0.91) and jump heights (p < 0.05; all d > 0.70) than the least mature group. No significant differences were observed in PFrel across the jumping tests, although measures of relative peak power (PPrel) did significantly increase with maturity. All sprint-speed measures, standing long jump (SLJ) distance and vaulting vertical take-off velocity were significantly greater in the more mature gymnasts (p < .001; d > 0.65). Thus, 4 maturation appears to have a significant influence on absolute isometric and dynamic forcetime variables, sprint speed and vaulting vertical take-off velocity. Chapters 4-6 also indicated that across all tests, peak speed during a 20 m sprint protocol has the strongest association with vaulting vertical take-off velocity (R2 = 59%) and also identified the ratio of vertical to horizontal take-off velocity (Ratiovert-hori) as a secondary determinant (R2 = 12 %). Multiple regression analyses also revealed that of the jumping protocols, ground contact time (GCT) and centre of mass displacement (COM?) from the drop jump [DJ] (14 %), combined with maturity status (41 %) had the highest predictive ability of vertical take-off velocity (R2 = 55 %). However, the IMTP failed to explain a large amount of variance (R2 = 15%). Data indicate that maturation influences vaulting vertical take-off velocity in young female gymnasts. Furthermore, our results highlight the importance of targeting peak sprint speed alongside take-off technique to develop gymnasts' ability to transfer linear speed to vertical take-off velocity. Study 4 (chapter 7) showed young female gymnasts significantly improved various kinetic determinants of strength and power, sprint speed and vaulting take-off velocity after participating in 10-months of supplementary neuromuscular training (GYM+NMT); changes that were not typically evident in the gymnastics-training only (GYM) or maturity-matched control (CON) groups. Analyses revealed that the observed significant adaptations in the GYM+NMT training group occurred at different stages of the 10-month training program and varied in magnitude (p < 0.05; g = 0.44-1.15). Isometric PFabs, horizontal jump distance and Peakmomentum during sprinting significantly improved at each testing session from baseline. After 7-months of NMT, significant improvements were shown in isometric PFrel, CMJ height and RSI and jump height in the DJ. The NMT stimulus took longer to transfer to sprinting and 5 vaulting performance, with peak sprint speed, spring-like behaviour in the DJ, and vaulting vertical take-off velocity significantly improving after 10-months. Overall, the findings from this study indicate that supplementary NMT can stimulate improvements in strength, power, speed and vaulting performance above and beyond those achieved through gymnastics training alone.